The physical elements in the design of cartoon illustrations affect the emotional perception of people from different cultures and age groups - Tongchung, Patcharin; Phaholthep, Charanya; Bunyasakseri, Thirawut (Edelweiss Applied Science and Technology, 2025)
This study focuses on the effects of the perception of physical elements on the perception of emotions and communication with cartoons of people of different ages and cultures classified by nationality and age range. The objectives of this research were: 1) to analyze the physical characteristics that affect emotional perception and communication; 2) to analyze and compare the relationship between the physical elements of an image comprising cartoons, emotional perception, and communication. This was a quantitative and qualitative study with a population and sample of 300 volunteers from three nationalities and three age groups: Thai, Japanese, and American. The tools used in this study were questionnaires and interviews using a 5-level estimation scale. Data analysis utilized statistics for comparative analysis and determined the mean and standard deviation. The results showed that the emotional and sensory perception levels were very high, with a mean of 4.06 and standard deviations of 0.89. Emotional characteristics create emotional perception and strengthen emotional awareness, which are at a high level, with a mean of 3.95 and a standard deviation of 0.95. Characters and scenes create emotional perception; deformed character ratios create emotional and sensory perception; natural scenes generate emotional and sensory perception; 2D shapes can generate emotional and sensory perception; depth of field generates emotional and sensory perception; and light and shadow generate moderate emotional and sensory perception, with a mean of 3.80 and standard deviations of 0.97. The scene produced a low level of emotional and sensory perception, with a mean of 3.66 and standard deviations of 1.07. Large characters generate very little emotional perception, with a mean of 3.52 and a standard deviation of 1.04. However, the analysis also shows that a p<0.05 value is considered statistically significant. Similarly, the interviews showed that the artistic elements were at the highest level of perception generation, and they were also able to analyze and compare physical characteristics according to the set objectives.